KAJIAN STANDAR PELAYANAN MINIMAL (SPM) BIDANG JALAN DI KABUPATEN NAGAN RAYA - Hendra Elfriadi; Sugiarto Sugiarto; Irin Caisarina (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
As one of the district that engage on the agriculture and plantation sector, Nagan Raya needs to be supported the facilities and infrastructure correspondingly, quality of transportation, and appropiate in MSS that mobility of goods and services can run smoothly. Anonymous (2015) had been defining of the planned local activity center ( LAC), regional activity center (RAC), Environment service center ( ESC), and classification of system network road. The purpose of this research are to evaluate the  practice MSS of road field in Nagan Raya, to specify MSS of road field based on connectivity indicator between region that accordance with SP in Nagan Raya, and also to evaluate fulfillment Minimum Service Standard of road field based on presentation indicator of road condition level in Nagan Raya. This reasearch conducted with collecting the datas that are Hamlet Neighbour book in Nagan Raya, condition data, and DFAA. The use of connectivity MSS on 2015 in Padang Rubek - Lueng Baro is 91,29 percent, Babussalam – Lueng Baro is 91, 78 percent, and Alue Bilie – Lueng Baro is 90,4 percent. The value of roadcondition by made the survey of road condition with visual method categorized at good (B), and medium (S) with each amount are 90,78 percent, and 9,22 percent. The value of road condition by made the survey of specific road condition categorized at good in the amount is 96, 51 percent, medium in the amount is 1,94 percent, and lightly damaged in the amount is 1,55 percent. The compliance of road field in Nagan Raya by made survey of specific road condition in the amount is 164,10 percent, meanwhile on the survey of road condition in visual method in the amount is 166,67 percent